Reality matters: in-field validation of fresh frozen cadaver-based airway training in HEMS - the BOAH Initiative: a prospective observational cohort study - Sebastian Imach; Tobias Ahnert; Sarah Krueger; Mai Bui; Bernd A. Leidel; Jenny Patricia Kehrberger; Michael Kemper; Benny Kölbel (BMC Emergency Medicine, 2026)
Abstract Background Endotracheal intubation (ETI) remains the gold standard for emergency airway management. The performance indicator is the first-pass success rate (FPSR). Providers without routine practice in elective airway management need adapted training to gain proficiency and maintain a high level of competence. Fresh frozen cadavers (FFCs) have been shown to be effective in training and can be modified to recreate difficult airway features seen in helicopter emergency service (HEMS). Methods In this prospective before-and-after study, the BASELINE phase consisted of recording both the performance of 16 HEMS physicians during 60 consecutive ETIs at Cologne HEMS and the corresponding airway characteristics of the patients. FPSR-raising measures for emergency airway management were identified through a structured literature review process and compiled into a bundle—the Best Of Airway management in HEMS (BOAH) bundle. The bundle was trained on five modified FFCs representing airway characteristics of the BASELINE phase. All the HEMS physicians and eight HEMS technical crew (HEMS-TC) members who were part of the BASELINE phase completed the training with videolaryngoscopy (VL) and a bougie-first strategy. Subsequently, another continuous 60 ETIs by the same teams were evaluated (BOAH phase). The primary outcome measure was the FPSR before and after the implementation of FFC training. Second, we evaluated the duration of ETIs and the oxygen saturation (SpO2) after ETIs. Results In the BOAH phase, 61 of 63 ETIs were recorded with a complete dataset by sixteen HEMS physicians. The FPSR significantly improved from the BASELINE (76.7%, 95% CI ±10.7) to the BOAH phase (95.1%, 95% CI ± 5.4, p=.004). Lowest postintubation oxygen saturation was 83.8% ± 16.1 SD (BASELINE) vs. 88.4% ± 13.5 SD (BOAH, p=0.014), and the duration of successful ETI attempts was 34 s ± 24.1 SD in the BASELINE phase and 32 s ± 14.9 SD in the BOAH phase (p=0.41). Conclusion The combination of the BOAH airway bundle and FFC-based training was associated with a higher observed FPSR and improved oxygenation outcomes when it was used on real emergency patients by non-anaesthetist-staffed HEMS crews. These results suggest that skills acquired during cadaver-based training, which included practice of a comprehensive airway bundle, can be reliably transferred to real-life missions.